Free transfer, limited mobility: A decade of higher education reform in Egypt and Morocco - Florian Kohstall (Revue des Mondes Musulmans et de la Méditerranée)
This article aims to demonstrate how countries with a relative low performance in higher education like Egypt and Morocco, are informed and worked by the forces of internationalization in this domain. It compares the path of university reforms in both countries over the last decade, from their emergence on the agenda to their implementation. Through the lenses of a public policy approach it illustrates how higher education is subject to a complex negotiation process between international organizations and domestic policy-makers. The transfer of international models like grant-based funding and the Bologna process has become the driving force of these reforms. But when imposed through a top-down approach these models do not necessarily bring about the outcome they might have promised. They rather illustrate an example of distorted internationalization.